Atividade física de escolares quilombolas durante o período de isolamento social causado pela pandemia de COVID-19 - Almeida, Erivelton de Oliveira (Brasil, 2023)
Child inactivity has grown too much with social isolation, which has worried researchers and health agencies that deal with the child population. The objective of this study was to investigate the physical activity and sedentary habits of quilombola students during the period of social isolation caused by the COVID-19 pandemic. The sample consisted of 60 quilombola students (41.7% boys), aged between 7 and 11 years. As an instrument, we used the Questionnaire for the Evaluation of Physical Activity and Sedentary Lifestyle in children and adolescents adapted to the reality of quilombola communities. The design consisted of four phases: 1) Initial contact with the Municipal Secretary of Education of the Municipality of Barreirinha to obtain authorization to carry out research in schools in quilombola communities; 2) Contact with administrators of quilombola schools; 3) Sending envelopes to schools, addressed to those responsible, containing the Free and Informed Consent Form; 4) Interview with the students to complete the questionnaire. It was observed that 75% of the investigated quilombola students practice physical activity a few times a week. The most reported physical activities were: playing ball (37%), classified as intense physical activity and walking (58%), classified as light physical activity. Boys practice more intense physical activity (170min/week) and girls, light physical activity (66min/week) and sedentary (275min/week). Only 36.6% of quilombola students meet the recommendation of the World Health Organization regarding the minimum time of physical activity practice. In short, quilombola students have more sedentary lifestyles during the pandemic period. It is suggested that future studies monitor the physical activity habits of this population to see if they are permanent or if they are just a picture of the pandemic scenario.